Switchable Dual-Wavelength Q-Switched Erbium-Doped Fibre Laser using Spider Silk as a Biocompatible and Eco-Friendly Saturable Absorber - Muhammad, N.A.M.; Awang, N.A.; Supaat, M.I. (2024)
This work aims to study the dual-wavelength Q-switched fibre laser performances with erbiumdoped fibre as the gain medium and the fibre Bragg gratings to allow stable switchable dualwavelength states. Spider silk was used as an alternative biological material for saturable absorber. The spider silk as a saturable absorber was prepared by directly sandwiched between the surface of fibre ferrules. A dual-wavelength system operating at 1550 nm and 1560 nm was generated by modulating the polarisation controller to regulate the mode competition in the ring cavity. This allows for a flexible switch between individual wavelengths of 1550 nm or 1560 nm. The device operates at a wavelength of 1550 nm, with 26.63 kHz repetition rate and 9.45 µs pulse width. At a wavelength of 1560 nm, it produces a repetition rate of 24 kHz and a pulse width of 10.47 µs. The output demonstrated consistent stability throughout time, with no changes recorded. This indicates a stable signal-to-noise ratio of 41.12 dB and 34 dB for wavelengths 1550 nm and 1560 nm, respectively. This study presents the latest approach using spider silk as a saturable absorber to create a dual-wavelength Q-switched fibre laser. The laser is based on a fibre Bragg gratings device and has potential uses in terahertz signal and laser radar.